Analysis of reduced paramagnetic shifts as an effective tool in NMR spectroscopy. Issue 2 (21st December 2021) - Pavlov, Alexander A.; Novikov, Valentin V.; Nikovskiy, Igor A.; Melnikova, Elizaveta K.; Nelyubina, Yulia V.; Aleshin, Dmitry Y.
Abstract : The concept of reduced paramagnetic shifts (RPS) is a useful approach to analyze the NMR spectra of paramagnetic transition metal complexes. Abstract : A recently introduced concept of reduced paramagnetic shifts (RPS) in NMR spectroscopy is applied here to a series of paramagnetic complexes with different metal ions, such as iron(ii ), iron(iii ) and cobalt(ii ), in different coordination environments of N-donor ligands, including a unique trigonal-prismatic geometry that is behind some record single-molecule magnet behaviours. A simple, almost visual analysis of the chemical shifts as a function of temperature, which is at the core of this approach, allows for a correct signal assignment and evaluation of the anisotropy of the magnetic susceptibility, the key indicator of a good single molecule magnet, that often cannot be done using traditional techniques rooted in quantum chemistry and NMR spectroscopy. The proposed approach thus emerged as a powerful alternative in deciphering the NMR spectra of paramagnetic compounds for applications in data processing and storage, magnetic resonance imaging and structural biology.